HUBUNGAN ANTARA PENGETAHUAN TENTANG PROSES PERSALINAN DENGAN TINGKAT KECEMASAN DALAM MENGHADAPI PERSALINAN PADA IBU HAMIL DI WILAYAH SUKOHARJO - Sri Aminingsih; Agatha Grace Anggraini (KOSALA : Jurnal Ilmu Kesehatan, 2016)
AbstractKnow can be defined as considering a items which have been studied previously. Thismatter can be interpreted that pregnant mother which have owned previous experienceor knowledge will affect at behavior, in this case is anxiety which can happened atpregnant mother when previously do not obtain knowledge about labour process.Pursuant to brief interview at some pregnant mother say that in this time experience ofanxiety because will face labour. Some pregnant mother tell not yet had experience bearand do not know how process bear which in fact when can bear normally. The purpose ofthis study was to know knowledge relation about labour process with anxiety level in faceof labour.The Subjects who involed as population in this research were 52 womans who pregnantin trimester II and trimester III. This research represent analytic research with desainresearch of correlation. While used by plan is sectional cross.From result of Pearson Corelation SPSS version program test 18.0 with = 5% ( 0.05)obtained p equal to 0,001 so that assess p < 0.05, with result of correlation - 0,928. It canbe conclusion that is negative correlation between knowledge with anxiety level in face ofcopy process pregnant mother in Sukoharjo region.Keywords: Knowledge and anxiety level.